48 Genetic study of horn fly abundance in beef cattle. (30th November 2020) - Ling, Ashley; Krause, Taylor; Heins, Bradley; Hinkle, Nancy; Pringle, Dean; Aggrey, Samuel E; Rekaya, Romdhane
Abstract: Disturbing the non-symbiotic relationship between horn flies and cattle is of economic, health, and animal welfare importance. Reliance on management and insecticides has proven inadequate. In the United States, horn flies are estimated to cause more than 1 billion in economic losses on pastured cattle annually. Although insecticides provide temporary control, their efficacy is hampered by several factors. Intensive insecticide use has led to horn fly resistance and decreased predation on horn flies by other insects. Due to the cost and logistic complexity of measuring fly resistance traits under commercial conditions, the genetic basis of these traits remains largely unknown. Only a few heritability estimates are available based on small-scale studies. Currently, the economic injury threshold (EIT) due to horn fly abundance (onset of production decay) is set at around 200 flies for beef cattle. This threshold is largely heuristically set. Additionally, the rate of decay in performance as a function of fly abundance after injury onset is unknown. It is also likely that EIT is breed and animal specific. Data used in this study was collected during the summer of 2019. Animals were not treated or managed in any way to control horn flies prior to data collection. Animals were assessed subjectively and based on image counts for horn fly abundance. Estimates of heritability of horn fly abundance ranged between 0.14 and 0.22 for subjective and image-based phenotypes. The lowest heritability was for the subjective assessment, likely due to the excessive variation between evaluators. Changepoint model-based analysis showed that EIT is variable between sire families, ranging from 265 to 413 flies. Furthermore, there was significant difference in the decay of performance after the onset of injury. The rate of decay ranged between -0.0003 and -0.00018. Collectively, these results indicate the potential to improve horn fly resistance/tolerance using genetic tools.